MARBLE WASTE AND FLY ASH UTILIZATIONS FOR FINE CERAMIC RAW MATERIALS - SUBARI SUBARI; SURIPTO SURIPTO (Indonesian Mining Journal, 2010)
The possibility of using marble waste and fly ash taken from a textile industry as raw materials for producing fine ceramics was studied. Besides those two materials, clay was also used as the formed agent for ceramic body. There were four compositions noted as T1, T2, T3 and T4 that consist of marble waste 10 %, fly ash 10– 25 % and clay 65 – 80 %. They were formed by the method of slip casting.The tests pieces of these fine ceramic bodies were then fired at temperature of 600 °C. The glaze were applied to the bodies and further fired at temperature of 1150 °C in a gas kiln. Characterization results of those four composition tests show that the composition of T2 (70 % of clay, 10 % of marble waste and 20 % of fly ash) gives the best result.